Aplikasi Lesson Study dalam Meningkatkan Kompetensi Profesional Guru di Madrasah Aliyah Bustanul Ulum Kota Langsa - Nursamsu Nursamsu; Allif Syahputra Bania; Elfrida Elfrida (Jurnal Pendidikan Biologi, 2018)
The purpose of the study was to describe the lesson study learning process. The application of lesson study is in the form of a cycle of planning, implementation, and reflection. This research method is research in the form of class action (action research) which consists of two cycles. Data retrieval is done by observation sheet to the model teacher in carrying out biology learning activities, interviews and questionnaires. Furthermore, the data analysis technique in the complete study uses three simultaneous activities, namely; (1) data reduction; (2) data presentation and (3) inference and verification of data. The results of this study consisted of two cycles: (1) Cycle I of the application of lesson study learning stages was categorized good with a value of 81.66%; (2) Cycle II is the advanced stage of the results of weaknesses and shortcomings in the first cycle, at this stage the lesson study learning application is categorized good with a value of 89.58%. Then it can be concluded that the lesson study learning application can improve teacher professional competence, and make the learning atmosphere active and creative, so students are enthusiastic to learn.